The effects of light and temperature on microalgal growth and nutrient removal: an experimental and mathematical approach - Ana L. Gonçalves (2016)
Cultivation of microalgae and cyanobacteria has been intensified in the last decades, due to the numerous applications described for these microorganisms. However, the high process costs associated with biomass production systems reduce the economic feasibility of microalgal/cyanobacterial cultivation. A better understanding of the effects of light and temperature on growth kinetics will contribute to the improvement of biomass productivities and reduce the costs associated with the optimization of culture parameters. In this study, the effects of average daily light irradiance and temperature on growth and nutrient removal were assessed using Chlorella vulgaris, Pseudokirchneriella subcapitata, Synechocystis salina and Microcystis aeruginosa. Additionally, a mathematical model relating specific growth rates with these variables was developed. Both kinetic growth parameters and nutrient removal had similar responses to light and temperature: increasing light supply, higher specific growth rates, biomass productivities and nutrient removal efficiencies were achieved. Among the studied temperatures, all microorganisms presented higher biomass productivities and nutrient removal efficiencies at 25 degrees C. Regarding the results from the mathematical model, the optimal temperature for the selected microorganisms was 25.3 +/- 1.1 degrees C. On the other hand, the optimal average daily light irradiances varied with the species, being 208, 258, 178 and 140 mu E m(-2) s(-1) for C. vulgaris, P. subcapitata, S. salina and M. aeruginosa, respectively.